Association between the Length of Hospital Stay and 30-Day Outcomes in Patients Admitted with Acute Decompensated Heart Failure - Melika Namvar; Mohammad Fakhrolmobasheri; Sadegh Mazaheri-Tehrani; Maryam Heidarpour; Maryam Emamimeybodi; Davood Shafie (Emergency Medicine International)
Background and Aim. Regarding patients admitted with acute decompensated heart failure (ADHF), there are inconsistent reports surrounding the association between length of stay (LOS) and mortality or rehospitalization following discharge. This study evaluates the association between LOS and 30-day outcomes after discharge in patients admitted with ADHF. Method. This study is performed in the context of the Persian Registry of Cardiovascular Disease/Heart Failure (PROVE/HF). We included all patients admitted with ADHF regardless of the etiology of heart failure (HF). LOS was classified in tertiles (<4 days, >4 and <6 days, and >6 days). Our outcomes were 30-day all-cause mortality and rehospitalization. Baseline characteristics and outcomes are reported according to the tertiles of LOS. A binary logistic regression and cox regression analysis were performed to evaluate the association between LOS and rehospitalization and death, respectively. Results. Between April 2019 and March 2020, 385 patients with ADHF were registered in our study. The mean length of hospitalization was 6.35 ± 5.46 days, varying from a minimum of 0 days to a maximum of 47 days. One hundred patients had a hospital stay lower than 4 days; 151 individuals had an intermediate LOS (4–6 days); and 134 were hospitalized for more than 6 days. Our analysis indicated no association between LOS and 30-day rehospitalization and death in multivariable or univariable models. Conclusion. This study found no association between LOS and rehospitalization or death in patients admitted with ADHF; however, further investigations are warranted.